ANALISIS PERNYATAAN STANDAR AKUNTANSI KEUANGAN (PSAK) NOMOR 16 TAHUN 2011 TERHADAP AKUNTANSI AKTIVA TETAP BERWUJUD PADA BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN CABANG WATAMPONE - Nurkurniana Nurkurniana (Magister Akuntansi, Universitas Atma Jaya Makassar, 2019)
This research is motivated by the fact that BPJS Health has business activities implementing social security. Each part of this organization takes an important part in presenting services to clients, so that many use fixed assets in their operations. The acquisition of fixed assets requires significant investment, good asset management, and reliable procedural implementation in accordance with the provisions of PSAK Number 16 of 2011 which regulates the accounting treatment of fixed assets. For this reason, it is necessary to know how the accounting treatment for tangible fixed assets at the BPJS Health Branch of Watampone. This research is a qualitative research through a descriptive approach that will provide clear and accurate information and answers on how the presentation of tangible fixed assets in financial statements and analysis of PSAK No. 16 of 2011 on the accounting treatment of tangible fixed assets at the BPJS Health Branch Watampone. The location of this study is the Watampone Branch BPJS Health Office. This study lasted for approximately 3 months, namely January - March 2019. Methods of data collection in this study were interviews, observation, document review and literature study. The results of this study indicate that the Accounting treatment for Tangible Fixed Assets at Branch Health BPJS has not fully complied with the provisions of PSAK Number 16 of 2011.